PENGARUH KOMITE AUDIT, BOARD SIZE, PROPORSI DEWAN KOMISARIS INDEPENDEN, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) - Reny Rahayuningsih, 13.05.52.0189; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2017)
This study aims to examined and analyzed the effect of audit committee, board size, proportion of independent commissionerâs board, leverage and firm size to firm value on manufacturing companies listed in the Indonesia Stock Exchange. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the years 2012-2015 that reported complete annual report and published in Indonesian Capital Market Directory. Samples are included in the criteria of this study were 222 companies using purposive sampling method. This research data analysis methods using the multiple linear regression analysis.Â The results showed that audit committee and board size has significant positive effect on firm value. Proportion of independent commissionerâs board, leverage and firm size has no effect on firm value.Keywords:Â Firm Value, Audit Committee, Board Size, Proportion of Independent Commissionerâs Board, Leverage, Firm Size